Decoding ozone's impact on the cornea: disruption of barrier integrity and its molecular drivers - Yi Tian; Liping Li; Zhongmou Sun; Jiamin Liu; Chen Qiu; Ji Zhou; Xinghuai Sun; Yuan Lei (Ecotoxicology and Environmental Safety)
This study aims to investigate the influence of ozone exposure on mouse corneas and human corneal epithelial cells (HCEC) to better understand its impact on corneal health and the underlying molecular mechanisms. Elevated cyclic ozone exposure was applied to both mouse corneas and HCECs to assess its effects on corneal structure and cellular response. Ozone exposure induced corneal stromal thinning (27.88 %), increased epithelial thickness (22.44 %), and disrupted epithelial barrier function. Inflammatory responses and nitrative stress, marked by inflammatory cell infiltration and heightened 3-nitrotyrosine levels, coupled with the upregulation of NLRP3, caspase-1 were observed in mice cornea. Additionally, ozone exposure induced diminished cell viability, nitrative stress, and activation of the NLRP3/caspase-1/GSDMD pathway in HCECs, which were mitigated by anti-nitration agent MnTMPyP treatment. In summary, the study elucidated the mechanisms underlying ozone-induced corneal toxicity, highlighting nitrative stress and NLRP3 inflammasome-mediated pyroptosis. These findings suggest the importance of minimizing ozone exposure and also provide potential therapeutic strategies targeting nitrative stress and inflammasome activation to prevent ozone-related tissue damage.